Common sense, reasoning, & rationality - Elio, Renée (Oxford University Press, 2002)
While common sense and rationality have often been viewed as two distinct features in a unified cognitive map, this volume engages with this notion and comes up with novel and often paradoxical views of this relationship.
Description based upon print version of record.
Keywords: Reasoning.; Practical reason.; Commonsense reasoning.; Common sense.